Predictive analysis of instruction in science to students’ declining in-terest in science-An analysis of gifted students of sixth - and seventh-grade in Taiwan - Chia-Yen Hsieh (Universitas Diponegoro, 2020)
Students’ interest in science declines substantially in the transition from elementary to secondary education. Using students’ ratings of their instruction on the topic of oxidation-reduction reaction, we examined if changes in instructional practices accounted for differences in situational interest in science imagination instruction and enduring individual interest in science imagination between elementary and secondary school classrooms. Multilevel regression analyses were conducted for a sample of 162 sixth - and 161 seventh-grade gifted classrooms. The use of student experiments, the elicitation of student explanations, and lack of clarity accounted to varying degrees for disparities in science interest between grade levels. The impact of instructional practices on individual interest was mediated by situational interest.